БАДИИЙ МАТННИ СЕМИОТИК ТАҲЛИЛ ҚИЛИШДА МАТНЛАРАРО ПАРАДИГМАТИК МУНОСАБАТЛАР - Саидова, Р.А. (SCIENCE and SOCIETY, 2021)
The literary text, which is the source of the study of literature, consists of a system of signs from beginning to end. This paper discusses the semiotic analysis of the literary text and the formation of a paradigmatic relationship between the characters in the content.